PENGARUH PEMBIAYAAN BAGI HASIL TERHADAP TINGKAT PROFITABILITAS PADA BANK UMUM SYARIAH DI INDONESIA PERIODE 2011-2015 - Ria Azmayani; Makhdalena Makhdalena; Gani Haryana (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: Research on profit-sharing financing and profitability levels has been largely undertaken by previous researchers, but the results have not been consistent, ie some have influence and some have no influence. Thus, the researcher is interested to re-examine the profit-sharing financing and profitability level. The purpose of this study is to determine the effect of profit sharing financing to the level of profitability. The population of this study is the Sharia Commercial Bank in Indonesia which has the required data for the period 2011-2015 with a period of observation of 60 periods. The type of data from this study is secondary data sourced from the website of Bank Indonesia (www.bi.go.id). Data analysis using simple regression. The results showed that financing for the results have a positive effect on the level of profitability.Keywords: Profit Sharing Financing, Level Of Profitability